Transcervical resection of primary small cell carcinoma of the mediastinum – a rare case of thoracic malignancy - Ivoslav Ivanov; Dimo Mitev (Folia Medica)
Small cell carcinoma is a disease mainly of pulmonary origin, but in extremely rare cases it can also be observed as a primary mediastinal mass. Here, we present the case of a 48-year-old male patient with a clinical manifestation of superior vena cava syndrome and a CT scan showing a tumor mass in the upper mediastinum compressing the major vessels. A surgical intervention was performed – videomedistinoscopy with partial excision of the tumor from which primary small cell neuroendocrine carcinoma of the mediastinum was detected during histological and immunohistochemical analysis. Multimodal treatment was administered, and after the surgical intervention, the patient was treated with chemotherapy and radiotherapy. The patient was actively monitored, and 8 months after diagnosis, there was a lack of persistent symptoms. From the monitoring PET/CT scan, a minimal single focus with metabolic activity in the mediastinum was observed with significant reduction in tumor size and lack of compression on the mediastinal vessels.